2013
DOI: 10.1007/978-3-642-45221-5_38
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Parity Reasoning

Abstract: Propositional satisfiability (SAT) solvers, which typically operate using conjunctive normal form (CNF), have been successfully applied in many domains. However, in some application areas such as circuit verification, bounded model checking, and logical cryptanalysis, instances can have many parity (xor) constraints which may not be handled efficiently if translated to CNF. Thus, extensions to the CNF-driven search with various parity reasoning engines ranging from equivalence reasoning to incremental Gaussian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Experimental evaluation on SAT 2005 benchmarks instances showed that, when "not too large", such CNF translations outperform dedicated XOR reasoning modules. The successor [61] provides several comparisons of special-reasoning machinery with resolution-based methods, and in Theorem 4 there we find a general ACtranslation; our Theorem 9.2 yields a better upper bound, but the heuristic reasoning of [59,61] seems valuable, and should be explored further.…”
Section: Translations To Cnfmentioning
confidence: 83%
See 2 more Smart Citations
“…Experimental evaluation on SAT 2005 benchmarks instances showed that, when "not too large", such CNF translations outperform dedicated XOR reasoning modules. The successor [61] provides several comparisons of special-reasoning machinery with resolution-based methods, and in Theorem 4 there we find a general ACtranslation; our Theorem 9.2 yields a better upper bound, but the heuristic reasoning of [59,61] seems valuable, and should be explored further.…”
Section: Translations To Cnfmentioning
confidence: 83%
“…Conjecture 11.1 There exists X * : CLS → PC, which computes for an XORclause-set F ∈ CLS a CNF-representation X * (F ) in time 2 O(tw(F )) ·ℓ(F ) O(1) , where tw(F ) is the treewidth of the incidence graph of F . Theorem 7 in [62] shows a weaker form of Conjecture 11.1, where instead of the incidence graph the variable-interaction graph (or "primal graph"; recall Lemma 4.7) is considered, and where instead of (absolute) propagation-completeness only AC is achieved. Altogether there seem to be interesting general theorems and methods waiting to be discovered, targeting representations in PC.…”
Section: Open Problems and Future Research Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…, y k−1 ⊕ x k = ε, introducing auxiliary variables y i . We show that X 1 (S * ), where S * is obtained from S by considering all derived equations, is a GAC-representation of S. The derived equations are obtained by adding up the equations of all sub-systems S ′ ⊆ S. There are 2 m such S ′ , and computing a GAC-representation is fixed-parameter tractable (fpt) in the parameter m, improving Laitinen et al 2013 [14], which showed fpt in n.…”
Section: Introductionmentioning
confidence: 81%
“…Namely the general "meta theorem" is, that search for a solution, when done properly, and the underlying (hyper-)graph is "sufficiently acyclic" together with sufficient "local consistency" of the constraints (the F i ), can proceed without backtracking. 14 In [63,64] this is studied for binary CSPs (i.e., n(F i ) = 2 for all i ∈ I), while in [65,66] these considerations are generalised to non-binary CSPs; see [67] for an overview. Due to the importance of this basic result, we provide a self-contained (complete) proof.…”
Section: Acyclicitymentioning
confidence: 99%